Probiotics-Containing Mucoadhesive Gel for Targeting the Dysbiosis Associated with Periodontal Diseases - Giuseppe Giannini; Irene Ragusa; Giulia Nerina Nardone; Sara Soldi; Marina Elli; Piera Valenti; Luigi Rosa; Emanuele Marra; Daniela Stoppoloni; Emilio Merlo Pich (International Journal of Dentistry)
Objective. Periodontitis is a common disorder that leads to the loss of both tooth and personal well-being, contributing to worsen the risk for metabolic and cardiovascular diseases. Recently, probiotics, characterized by rapid oral dispersion, have been topically used. Here, we present data of a mucoadhesive gel containing probiotics, capable of ensuring a slow release of bacteria to prevent and treat periodontitis. Methods. An original mucoadhesive gel (AL0005) that is anhydrous and of food grade, loaded with the blend of lactobacilli and plants’ dry extracts, has been assayed. Results. The release kinetics of the bacterial mixture in different experimental models in vitro, including simulated saliva or physiological solutions, showed a significant and stable release for 5–8 hours. In one in vivo study of a mouse model of periodontitis, a locally applied mucoadhesive gel enriched with probiotic strains improved significantly the tissue pathology when compared with vehicle-exposed mice. Conclusions. Together, the results suggest that this mucoadhesive gel can be useful in the normalization of the gum bacterial flora and improvement of the tissue pathology of gum disorders.